The devil is in the details: a feminist perspective on development, women's rights, and fundamentalisms. Issue 1 (2nd January 2017) - Imam, Ayesha; Gokal, Shareen; Marler, Isabel
ABSTRACT: This article presents the Association for Women's Rights in Development's (AWID) perspective on the issue of religious fundamentalisms as they affect women's rights in the world today. Globally and in every religious context there has been a growth in the power and influence of religious fundamentalist actors. Although the violence that they are wreaking on women's rights and human rights may differ and manifest in specific ways depending on the context, it is clear that this escalation is taking place across the world. The article surveys the facts on the rise in fundamentalisms, and the reasons for this. It presents a set of recommendations to the development sector, to enable it to respond to the threats religious fundamentalisms present to gender equality and women's rights.